Out-of-pocket expenditure for institutional delivery in tertiary hospitals with and without aama program in Kathmandu Valley, Nepal: a comparative study. - Sankhi,Kripa (2020)
ABSTRACT: Introduction: Higher costs of maternity services has impeded maternal health service utilization. To address the financial barrier, Government of Nepal introduced demand side financing scheme, Aama program in government and some non-government facilities. The objective of the study was to compare the out-of-pocket expenditure for institutional delivery in tertiary hospitals with and without Aama program in Kathmandu valley. Methods: Hospital based cross-sectional comparative study was conducted in 424 women, 212 in each, who had delivered in the Aama facility and non-Aama facility. Stratified simple random sampling method was used for sampling. Data was collected through face to face interview method using semi-structured questionnaire. T-test and ANOVA test was used for comparing mean OOPE and multivariate analysis was done using multiple linear regression. Findings: The mean out-of-pocket expenditure (OOPE) in non-aama facility was NRs. 19051.94 and in Aama facility was NRs. 4159.45. When including transportation expenditure and non-medical expenditure to OOPE, mean total expenditure was NRs. 20816.33 and NRs. 24917.05 in non-aama facility and NRs. 5483.22 and NRs. 9841.05 in Aama facility respectively. There was significant difference in mean out of pocket expenditure between two facilities at p-value <0.001. Multiple regression model revealed that OOPE in non-aama facility was 140 percent more than that of Aama facility keeping all others independent variables constant (β coefficient- 1.407, CI 1.365 to 1.448). The difference in mean OOPE was statistically significant with ethnicity, mode of delivery, duration of hospital stay, history of previous C/S, multiple pregnancy, onset of labor, presentation of fetus and pregnancy complications in both the facilities with and without Aama program. Conclusion: Women seeking delivery care in tertiary facilities with Aama program are spending substantial amount on the services that are supposed to be provided free. However, in comparison to the other public facilities without Aama program, this program has showed lower OOPE and greater financial risk protection suggesting a need for strengthening of Aama program along with its expansion to other public and private facilities in near future.